2000
DOI: 10.1002/1521-3773(20000602)39:11<1995::aid-anie1995>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Constant Selectivity Relationships of Addition Reactions of Carbanions

Abstract: The selectivities of stabilized carbanions towards electron‐deficient π‐electron systems are nearly independent of their reactivities, as shown by the rate constants of the reactions of nine carbanions 2 with four quinone methides 1. These constant selectivity relationships may constitute the basis of a nucleophilicity scale for carbanions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
60
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 5 publications
3
60
0
4
Order By: Relevance
“…In ‹bereinstimmung damit berichteten wir, dass bei den Reaktionen von 1 j (Tabelle 2) mit 2 f-NBu 4 , 2 f-K, 2 f-K/ [18]Krone-6 und 2 f-K/Kryptofix 222 (4,7,13,16,21,24-Hexaoxa-1,10-diazabicyclo[8.8.8]hexacosan) die gleichen Geschwindigkeitskonstanten beobachtet wurden. [3] Daher ergibt die Division der beobachteten Geschwin- [*] Prof. Dr Tabelle 2. Strukturformeln und Elektrophilieparameter der Chinonmethi-…”
Section: Roland Lucius Robert Loos Und Herbert Mayr*unclassified
See 1 more Smart Citation
“…In ‹bereinstimmung damit berichteten wir, dass bei den Reaktionen von 1 j (Tabelle 2) mit 2 f-NBu 4 , 2 f-K, 2 f-K/ [18]Krone-6 und 2 f-K/Kryptofix 222 (4,7,13,16,21,24-Hexaoxa-1,10-diazabicyclo[8.8.8]hexacosan) die gleichen Geschwindigkeitskonstanten beobachtet wurden. [3] Daher ergibt die Division der beobachteten Geschwin- [*] Prof. Dr Tabelle 2. Strukturformeln und Elektrophilieparameter der Chinonmethi-…”
Section: Roland Lucius Robert Loos Und Herbert Mayr*unclassified
“…Anders als bei fr¸her untersuchten Carbokation-Carbanion-Kombinationsreaktionen [8] spielen Einelektronentransferprozesse hier keine Rolle. [3] sowie in Tabelle 3 dieser Arbeit wurden nun verwendet, um ausgehend von Gleichung (1) die Elektrophilieparameter E der Chinonmethide 1 g ± m sowie die N-und s-Parameter der Carbanionen 2 a ± h zu berechnen. [9] Alle Geschwindigkeitskonstanten der Reaktionen der Carbanionen 2 a ± h in Lit.…”
Section: Roland Lucius Robert Loos Und Herbert Mayr*unclassified
“…The correlation between the nucleophilicities and pK a values of carbanions is quite poor [9] much like the correlation between the N gas values in Table 2 and gas-phase basicities. However, the correlation between Mayrs E values and the E gas values in Table 2 is reasonable for most of the electrophiles ( Figure 5, R 2 = 0.978).…”
mentioning
confidence: 93%
“…Plot of (lg k)/s N versus the nucleophilicity parameter N for the reactions of benzhydryl cations and quinone methides with p-nucleophiles (in CH 2 Cl 2 ) and carbanions (in DMSO). 17 that purpose, 15 as they can be considered as oxy-substituted benzhydrylium ions, which again have the same steric environment around the reaction center. In cases where the attack of the carbanions XYCH À at the quinone methides was reversible, Roland Lucius studied the reactions in the presence of excess CH acids XYCH 2 , which protonate the intermediate phenolate ions and thus give rise to second-order kinetics with rate-determining CC-bond formation (Scheme 3).…”
Section: Construction Of the Nucleophilicity And Electrophilicity Scalesmentioning
confidence: 99%
“…In cases where the attack of the carbanions XYCH À at the quinone methides was reversible, Roland Lucius studied the reactions in the presence of excess CH acids XYCH 2 , which protonate the intermediate phenolate ions and thus give rise to second-order kinetics with rate-determining CC-bond formation (Scheme 3). 15 Since in dilute DMSO solution the measured rate constants for the reactions of the potassium salts were not affected by 18-crown-6 additives and were identical to those measured for the corresponding tetrabutylammonium salts, we concluded that we were determining the reactivities of the free carbanions. A detailed study of the influence of counterions on the nucleophilicities of different types of carbanions was published recently.…”
Section: Construction Of the Nucleophilicity And Electrophilicity Scalesmentioning
confidence: 99%